Muda forzada o "reciclaje" de gallinas ponedoras en piso : resultados de estudios de campo - Zumbado Alpízar, Mario Ernesto 1955-; Solís S, Javier; Ureña Araya, Gustavo Adolfo 1961-2025 (1998)
Force molting of laying hens housed in littered floors. Results of field studies. Very little information is available on force molting of hen flocks housed in floors and litter facilities instead of cages. A field study was conducted with nine Isa-Brown flocks averaging 8,100 hens per flock, together with information from one Isa-Babcock B-300 white hen's flock. A conventional fasting, no artificial light molting program, was implemented in all flocks The fasting period averaged 13.2 days, with a minimum of 9 and a maximum of 15 days. This was the necessary period of time for the flocks to stop laying eggs and lose enough body weight. Flocks stopped production at 12.2 days without feed (11 min, 13 max); however, two flocks never stopped laying hens, and their lowest laying rate was 0.9 and 0.4% hen-day. The white flock halted production after 6 days of fasting. Average weight loss for the brown hens was 20% and 24.2% at 10 and 14 days of fasting, respectively (18.3 and 27.3% for the white flock). The daily weight loss ranged from 1.7 to 2.2%. The day previous to start the molting program, the average laying rate was 70.3% hen-day (60.0-78.8%) at 70.6 (65.0-76.0) weeks of age From the first egg after molting to 50% production, the flock averaged 17.6 (13.0-22.0) days, and peak egg production was 77.2% (67.2-84.2%) hen-day. It took the brown hen flocks an average of 34 days to reach 50% egg production from the first day of fasting. The white flock lasted 41 days to reach 50% production. The brown flocks reached 6.9% (1.9-10.7%) egg production above the level they had the day prior to the start of the molting program and stayed 12 (6-21) weeks above that laying rate value. They remained for 2.2 (0-8) weeks above 80% hen-day egg production. Hen mortality averaged 0.35%/week (0.11-0.85) during the 40 days after fasting started. These data with hens on littered floors are quite different compared to the information available on force molting...
Dada la escasa información disponible sobre los procedimientos y resultados de la muda forzada con gallinas ponedoras alojadas en galpones de piso y no en jaulas, se realizó un estudio con 9 lotes comerciales de gallinas Isa Brown de huevo marrón con un promedio de 8100 gallinas por lote. Además, se analizaron los datos de 1 lote de gallinas blancas Isa Babcock B-300. En todos los lotes se utilizó un método convencional de ayuno y eliminación de luz artificial para forzar a las gallinas a detener la producción de huevos En promedio, el período de ayuno fue de 13.2 días, con un mínimo de 9 y un máximo de 15 días, tiempo necesario para que los lotes dejaran de producir y las aves perdieran suficiente peso. En promedio, los lotes detuvieron su producción de huevos a los 12.2 días de ayuno (11 min, 13 máx.), aunque 2 lotes no dejaron totalmente de producir, alcanzando mínimos de 0.9 y 0.4 por ciento de postura de gallina al día. Las gallinas blancas tuvieron postura a los 6 días de ayuno. La pérdida de peso promedio de las gallinas rojas fue de 20 y 24.2 por ciento a los 10 y 14 días de ayuno respectivamente (18.3 y 27.3 por ciento para las blancas), con un rango promedio de pérdida de peso de 1.7 a 2.3 por ciento diario. El día anterior al ayuno, los lotes promediaron 70.3 por ciento (60.0-78.8 por ciento) de postura de gallina día a una edad de 70.6 (65.0-76.0) semanas. Reiniciaron la postura alcanzaron el 50 por ciento de producción a los 17.6 (13.0-22.0) días y el máximo o pico de altura fue de 77.2 por ciento (67.2-84.2 por ciento) de gallina día En total, los lotes tardaron un promedio de 34 días en alcanzar el 50 por ciento de postura contada desde el primer día de ayuno. El lote de gallinas blancas tardó 41 días en llegar al 50 por ciento. Los lotes obtuvieron un 6.9 por ciento (1.9-10.7 por ciento) de postura por encima del nivel de producción previo al inicio del programa de muda y estuvieron 12 (6-21) semanas...
En revista Nutrición Animal Tropical, vol. 4, no. 1 (enero-junio 1998)
Descripción basada en el contenido visto el 03 de setiembre, 2025